Russian fiscal policy during the financial crisis - Alexey A. Ponomarenko; Sergey A. Vlasov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
This study examines the expanding role of fiscal policy at a time of financial crisis. It analyses the stimulative fiscal measures of the Russian government in 2008-2010 and compares these with simi-lar actions taken in other countries. The risks and limitations associated with the development and implementation of the measures are analyzed. The macroeconomic effects of the fiscal policy measures are estimated using a structural vector autoregressive (SVAR) model, the fiscal multip-liers are calculated, and factors influencing multiplier size are examined.
URN:NBN:fi:bof-201408072180
Keywords: 330